Participative research for individualised care in cardiovascular diseases (PRIC-CVD): study protocol for a non-interventional, multicentre mixed-methods study as part of iCARE4CVD - Bianca Steiner; Hans-Peter Brunner-La Rocca; Loreena Hill; Bettina Zippel-Schultz; Julia Brandts; Matthew Barrett; Thomas Maria Helms; Sabine Friedl; Marlo Verket; Karolien Baldewijns; Marguerite Murphy; Anne McNulty; et al. (BMJ Open)
Introduction Cardiovascular disease (CVD) represents a public health burden, with high prevalence and significant morbidity and mortality. Although evidence-based interventions exist, there is a need for more individualised care. The European project Individualised care from early risk of cardiovascular disease to established heart failure (iCARE4CVD) aims to personalise CVD prevention and treatment. Participatory health research, which actively involves patients in the planning, implementation and evaluation of projects, plays a crucial role here. However, patient participation is often unsuccessful due to the lack of a representative patient sample who is involved throughout the project’s duration, has knowledge of the project and can contribute their experience.Methods and analysis Participative Research for Individualised Care in Cardiovascular Diseases is a non-interventional, non-randomised, multicentre mixed-methods study. The aim is to incorporate patients’ insights into several key activities within iCARE4CVD by establishing country-specific patient panels in Belgium, Germany, Ireland and the UK. The primary objective is to identify patients’ preferences, experiences, requirements and needs for better diagnosis, treatment and self-care of CVD. Therefore, 10–12 patients across the CVD spectrum, from early risk to established CVD and heart failure, will be included in each country (40–48 in total). Over 3.5 years, patient panel members are required to complete four tasks: (1) identification of meaningful Patient-Reported Outcome and Experiences Measures, (2) development of a motivational model to increase adherence, (3) feedback on CVD care processes and (4) usability testing of new digital tools developed within iCARE4CVD. These tasks comprise eight activities in the form of paper-based or digital exercises, telephone surveys, written surveys and in-person focus groups. The results will be continuously incorporated into iCARE4CVD.Ethics and dissemination This study received ethical approval by the Ethics Committee at the Faculty of Medicine of RWTH Aachen University (EK 24-172) and St. Vincent’s University Hospital (RS24-027), Research Ethics Committee. In Geel and Belfast, positive ethics approval is pending. All participants will provide written informed consent prior to enrolment in the study and participation in the first patient panel task. Results will be published in peer-reviewed journals and presented at scientific conferences.Trial registration number DRKS00034899.Protocol version V2.1, 6 June 2024.